Pengaturan Pengelolaan Limbah Cair Bahan Berbahaya dan Beracun di Indonesia Serta Implementasinya oleh CV. Master Laundry di Kabupaten Bandung - Nurjulianto, Fariz; Frency Siska (UNISBA Press, 2024)
Abstract, every business and/or activity that generates hazardous waste is required to conduct hazardous waste management either independently or by using hazardous waste management services by other parties. Hazardous waste management must have a license. CV Master Laundry, one of the businesses in Bandung Regency, manages hazardous waste independently without having a license and manages hazardous waste that is not in accordance with the UUPPLH, PP on Hazardous Waste Management, and Bandung Regency Regional Regulation No. 2/2018 on Hazardous Waste Management. This research aims to understand the regulation of hazardous and toxic liquid waste management in Indonesia in relation to Bandung Regency Regional Regulation No. 2/2018 on Hazardous and Toxic Waste Management and its implementation by CV Master Laundry in Bandung Regency. This research uses a normative juridical approach method with the type of literature study research and analytical descriptive research specifications. The results of the study concluded that the regulation of B3 liquid waste management in Indonesia, which is related to the Bandung Regency Regional Regulation No. 2/2018 concerning B3 Waste Management, is that every business and / or activity is required to manage the B3 waste it produces, by reducing, storing, collecting, transporting, utilizing, processing, and / or stockpiling B3 waste, by obtaining a B3 waste processing license. The implementation by CV. Master Laundry in Bandung Regency is to process its own B3 waste but does not have a B3 waste processing license, so that the processing of B3 waste is also not in accordance with applicable regulations. Law enforcement against CV. Master Laundry that commits violations in the management of B3 liquid waste in relation to Bandung Regency Regional Regulation No. 2/2018 concerning Management and Control of Hazardous Waste can be subject to administrative law enforcement and environmental crimes. Abstrak. Setiap usaha yang menghasilkan limbah Bahan Berbahaya dan Beracun (B3) wajib melakukan pengelolaan limbah, baik mandiri maupun dengan menggunakan jasa pihak lain, dan harus memiliki perizinan. CV Master Laundry di Kabupaten Bandung terlibat dalam pengelolaan limbah B3 secara mandiri tanpa izin, melanggar UU Pengelolaan Limbah B3, PP Pengelolaan Limbah B3, dan Peraturan Daerah (Perda) Kabupaten Bandung No. 2/2018 tentang Pengelolaan Limbah B3.Penelitian ini bertujuan memahami regulasi pengelolaan limbah cair B3 di Indonesia terkait Perda Kabupaten Bandung No. 2/2018 dan implementasinya oleh CV. Master Laundry di Kabupaten Bandung. Metode penelitian yang digunakan adalah pendekatan yuridis normatif dengan studi kepustakaan, bersifat deskriptif analitis.Hasil penelitian menunjukkan bahwa setiap usaha harus mengelola limbah B3 dengan kegiatan pengurangan, penyimpanan, pengumpulan, pengangkutan, pemanfaatan, pengolahan, dan/atau penimbunan, serta harus memiliki perizinan pengelolaan limbah B3. CV. Master Laundry di Kabupaten Bandung, meskipun melakukan pengolahan limbah B3, tidak memiliki izin yang sesuai dengan peraturan. Pelanggaran ini dapat dikenakan penegakan hukum administratif dan pidana lingkungan hidup sesuai Perda Kabupaten Bandung No. 2/2018.